2022
DOI: 10.3390/jcm11154617
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Condition among University Students of Bangladesh during the Critical COVID-19 Period

Abstract: Bangladesh’s education sector has been in a state of flux since COVID-19. During the pandemic, all university campuses were closed. There was a mental health issue among the students. This study aims to examine the mental health condition and the determinants that contribute to adverse mental health conditions among university students of Bangladesh. A survey was performed online among university students in Bangladesh, in mid-June 2020 when averaging 3345 affected cases of the population daily. The convenienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…47 High emotional intelligence could significantly alleviate the anxiety, maintaining mental health for students during the pandemic. 12 , 13 Moreover, it has been shown that psychological support might mitigate the effect of COVID-19-caused stress in university students in Bangladesh during COVID-19 pandemic 20 and that individuals with more psychological support had better mental health status. 19 In consistence with this principle, our study showed that at the same level of emotional intelligence, college students with a high psychological capital score had better self-rated health state than those with a low one.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…47 High emotional intelligence could significantly alleviate the anxiety, maintaining mental health for students during the pandemic. 12 , 13 Moreover, it has been shown that psychological support might mitigate the effect of COVID-19-caused stress in university students in Bangladesh during COVID-19 pandemic 20 and that individuals with more psychological support had better mental health status. 19 In consistence with this principle, our study showed that at the same level of emotional intelligence, college students with a high psychological capital score had better self-rated health state than those with a low one.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Female students were more anxious and stressed than males during COVID-19 pandemic in Bangladesh. 20 Taken together, we hypothesize that emotional intelligence, psychological capital and coping style are associated with self-rated health of college students during the COVID-19 pandemic in China. Thus, the purposes of this study were to investigate the associations among emotional intelligence, psychological capital, coping style and health status in college…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Psychological resilience, an ability to "bounce back" from a negative emotional experience and to confront stressful situations, is a major protective factor of burnout in nurses 17,18 . Moreover, a recent study reported that psychological support was positively associated with better mental health 19 , which might alleviate psychological impact in Bangladesh university students during COVID-19 pandemic 20 .…”
Section: Introductionmentioning
confidence: 99%